2017
DOI: 10.2147/dmso.s137571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin K supplementation on insulin sensitivity: a meta-analysis

Abstract: ObjectiveTo perform a systematic review and meta-analysis of randomized, placebo-controlled trials to assess the effect of vitamin K supplementation on insulin sensitivity.Data sourcesMEDLINE, the Cochrane Library, CINAHL, Web of Science, Scopus, clinicaltrials.gov, and clinicaltrialresults.org were searched up to January 2017. Reference lists of related papers were also scanned.Study selectionRandomized controlled trials were selected if they compared vitamin K supplementation with placebo or no treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Vitamin K supplementation only led to an improvement in CRP levels ( P = 0.01) and the insulin sensitivity index ( P < 0.001). Neither did Suksomboon et al (245) (8 RCTs and 1,077 participants) find any effect of vitamin K supplementation on insulin sensitivity after observing no changes in the parameters analyzed such as insulin resistance, fasting plasma glucose, fasting plasma insulin, CRP, adiponectin, leptin, or IL-6 levels. Similar results were described in the meta-analysis by Shahdadian et al (246) in which vitamin K supplementation had no significant effect on glycemic control in healthy subjects.…”
Section: Vitaminsmentioning
confidence: 86%
“…Vitamin K supplementation only led to an improvement in CRP levels ( P = 0.01) and the insulin sensitivity index ( P < 0.001). Neither did Suksomboon et al (245) (8 RCTs and 1,077 participants) find any effect of vitamin K supplementation on insulin sensitivity after observing no changes in the parameters analyzed such as insulin resistance, fasting plasma glucose, fasting plasma insulin, CRP, adiponectin, leptin, or IL-6 levels. Similar results were described in the meta-analysis by Shahdadian et al (246) in which vitamin K supplementation had no significant effect on glycemic control in healthy subjects.…”
Section: Vitaminsmentioning
confidence: 86%
“…However, studies of vitamin K2 supplementation in young men and women, and in postmenopausal women, have found no effect on adiponectin [ 139 , 140 ]. A systematic review of eight trials involving 1077 participants reported no effect of vitamin K supplementation on insulin sensitivity, concluding that further well-designed randomized controlled trials with large sample sizes are needed [ 141 ]. Vitamin K supplementation consistently reduced ucOC, increasing the proportion of carboxylated osteocalcin [ 135 , 136 , 138 , 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K supplementation consistently reduced ucOC, increasing the proportion of carboxylated osteocalcin [ 135 , 136 , 138 , 139 , 140 ]. Thus, the overall effect of vitamin K supplementation on indices of glucose metabolism remains to be fully clarified, reflecting the broader actions of vitamin K1 and K2 on pathways distinct from osteocalcin [ 141 , 142 , 143 , 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis assessed the effects of vitamin K supplementation on a homeostasis model assessment of insulin resistance (HOMA-IR), fasting plasma glucose and insulin, CRP, adiponectin, leptin, or IL-6 levels [ 129 ]. A total of eight trials involving 1077 participants met the inclusion criteria.…”
Section: How Can We Increase Adiponectin?mentioning
confidence: 99%